Synthesis Methyl Nitrophenyl Acrylate and Cytotoxic Activity Test against P388 Leukemia Cells - Teni Ernawati; Zulfa Khoirunni’mah (Indonesian Journal of Chemistry, 2015)
Synthesis of methyl nitrophenyl acrylate via modification of methyl trans-cinnamate had been done to improve its biological activity. The reaction of methyl trans-cinnamate with nitrating agent gave methyl 3-(2-nitrophenyl)acrylate and methyl 3-(4-nitrophenyl)acrylate with an ortho/para ratio of 1:8. Its structure was confirmed with 1H-NMR, 13C-NMR, FTIR, GC-MS. Biological activity of methyl 3-(4-nitrophenyl)acrylate and methyl 3-(2-nitrophenyl)acrylate assays was performed on Cancer cells against P388 Murine Leukemia with IC50= 7.98 μg/mL, IC50 = 27.78 μg/mL.